Real time monitoring critical parameters in tissue culture growth room with SMS alert system - Aziz N.H.A.; Muhamad W.N.W.; Wahab N.A.; Alias A.J.; Hashim A.T.; Mustafa R. (2023)
Real-time monitoring critical parameter is enhanced with email and short messaging system (SMS) for alert system. This system consists of four subsystems which include data acquisition, website monitoring, email protocol and SMS system. The aim of the integrated system is to remotely monitor critical parameter in tissue culture growth room. Research has shown that factors such as temperature, humidity, liquid, phase and gas compositions are critical in producing quality clonal materials using tissue culture process. Consequently, sensors are required to monitor and record the data in growth room. All sensors will monitor critical parameters that will be linked to the database and analysis software for storing and analyzing the monitored data. For the purpose of remotely monitor critical parameter, website and SMS enquiry are developed. The system would monitor via telemetry system and provide automatically email or short message (SMS) notifications upon identification of a disturbance module. 2010 IEEE.